Can tender and mature coconut water-mixed contrast media provide a diagnostically acceptable radiograph? - Sayed, Inayatullah Shah; Mohd Salleh, Nur Suhaili Syahirah; Syed, Waliullah Shah (2021)
Contrast materials are administered into the patient’s body for enhancing the diagnostic performance of imaging modalities in most radiology practices. Adverse effects of contrast material may appear as immediate or delayed reactions in patients. Literature shows that coconut water, contrast media and human blood plasma have some similar properties. Thus, we investigated the use of tender and mature coconut water-mixed radiographic contrast materials to provide a diagnostically acceptable radiograph. The pH and viscosity of coconut water was measured. Six tubes of polyvinyl chloride of 0.3 cm outer diameter, 10 cm long (simulating human blood vessels), filled individually with contrast media, tender, mature coconut water, air, tender coconut water-mixed contrast media and mature coconut water-mixed contrast media were scanned. Coconut water was obtained from coconuts of Pekan, Bukit Setongkol and Pancing Timur areas. Contrast materials used were Iopamiro 370 mg I/mL, Omnipaque 300 mg I/mL and Dotarem. Each piece of the tube was inserted into the hole of the Rando phantom. The phantom was exposed at different exposure settings (70 kVp with 20, 22 and 25 mAs) using Siemens Multix Top X-ray system. ImageJ and Image Quality Criteria Scoring were used to evaluate the image quality of radiographs. Results show that the visibility of tube with contrast media is still the highest in radiographs, in the order of Iopamiro 370 mg I/mL, Omnipaque 300 mg I/mL followed by Dotarem. Results show the mature coconut water-mixed contrast media has the second highest visibility followed by tender coconut water-mixed. From Pancing Timur mature coconut water-mixed Iopamiro 370 mgI/ml provided the highest visibility. In conclusion, tender and mature coconut water-mixed contrast media used in this study has the potential to provide reasonably good quality radiographs. Further investigations are required to test whether the adverse effects of contrast media can be minimized with coconut water-mixed contrast media.